Kajian Perubahan Kerapatan Vegetasi pada Kawasan Taman Wisata Alam Ruteng Site Hutan Lok Pahar Akibat Perambahan Hutan - Mersiana Yunita Primaya Cilik; Mamie E. Pellondou; Pamona Silvia Sinaga (Wana Lestari, 2022)
The activity of encroaching on the forest that occurs in the Ruteng Natural Park area site Lok Pahar forest to be used as agricultural land has had an impact, namely changes in the density of vegetation in the forest area. This study aims to examine changes in vegetation density in the Ruteng Nature Park area site Lok Pahar forest due to forest encroachment and examine efforts to prevent and control forest encroachment. The results showed that there was a change in vegetation density in the Ruteng Nature Park area based on the results of overlay NDVI (Normalized Difference Vegetation Index) on 2 Landsat 8 images, namely Landsat 8 Imagery in 2014 and in 2021. Changes in vegetation density in the Tourism Park area Alam Ruteng based on the results of the NDVI (Normalized Difference Vegetation Index) overlay on 2 Landsat 8 images, namely Landsat 8 Imagery in 2014 and Landsat 8 Imagery 2021. The results of the 2014 Landsat Image NDVI calculation, the forest density area in the sparse vegetation density class is 49 .95 ha, and decreased by 1.29% in 2021 to 32.46 ha. In 2014 the medium-level vegetation density class was 384.39 ha, and in 2021 it increased by 2.74%, the medium-level vegetation density class was 421.64 ha. Then, in the dense vegetation density class of 926.73 ha, it decreased by 1.45% so that the area of dense vegetation density class became 906.97 ha.